A comparative study of the role of monetary policies in achieving economic growth in some oil and non-oil countries during the period 1990-2017 - خلف, حميد حسن (Journal of Economics and Administrative Sciences, 2018)
The research problem was to identify the impact of monetary policies on economic growth in the oil and non-oil countries. The researcher chose the Republic of Iraq as an example for the oil countries and the Arab Republic of Egypt as an example for the non-oil countries to hold a comparison on the impact of monetary policies.The research found that the monetary policies and their tools in the Iraqi economy affect the rate of GDP growth by 73%, which shows the strong impact of monetary policies on the economic growth in the Iraqi economy as an example of an oil state. GDP growth rate of 61%, indicating the impact of monetary policies on economic growth in the Egyptian economy as an example of a non-oil state And that the impact of Iraqi monetary policies and tools is greater than the impact of the Egyptian monetary policies and tools during the period of study from 1990 to 2017. This may be due to the basic dependence of Iraq on oil in increasing the amount of money traded and the continuous rise in oil prices during that period, which is not available in the Egyptian economy Shows how different the impact of monetary policy on economic growth rates between oil and non-oil countries.The study recommended the use of monetary policies with a high impact on economic growth, increasing the effectiveness of the monetary policy tools used, as well as the need to work on increasing and diversifying sources of income and financing and not relying on one source of income in both Iraq and Egypt.